Short report: interim safety results for a phase II trial measuring the integration of stereotactic ablative radiotherapy (SABR) plus surgery for early stage non-small cell lung cancer (MISSILE-NSCLC). Issue 1 (December 2017) - Palma, David; Nguyen, Timothy; Kwan, Keith; Gaede, Stewart; Landis, Mark; Malthaner, Richard; Fortin, Dalilah; Louie, Alexander; Frechette, Eric; Rodrigues, George; Yaremko, Brian; Yu, Edward; et al.
Abstract A phase II trial was launched to evaluate if neoadjuvant stereotactic ablative radiotherapy (SABR) before surgery improves oncologic outcomes in patients with stage I non-small cell lung cancer (NSCLC). We report a mandated interim safety analysis for the first 10 patients who completed protocol treatment. Operable patients with biopsy-proven T1-2 N0 NSCLC were eligible. SABR was delivered using a risk-adapted fractionation (54Gy/3 fractions, 55/5 or 60/8). Surgical resection was planned 10 weeks later at a high-volume center (>200 lung cancer resections annually). Patients were imaged with dynamic positron emission tomography-computed tomography scans using18 F-fludeoxyglucose (18 F-FDG-PET CT) and dynamic contrast-enhanced CT before SABR and again before surgery. Toxicity was recorded using CTCAE version 4.0. Twelve patients were enrolled between 09/2014 and 09/2015. Two did not undergo surgery, due to patient or surgeon preference; neither patient has developed toxicity or recurrence. For the 10 patients completing both treatments, median age was 70 (range: 54–76), 60% had T1 disease, and 60% had adenocarcinoma. Median FEV1 was 73% predicted (range: 54–87%). Median time to surgery post-SABR was 10.1 weeks (range: 9.3–15.6 weeks). Surgery consisted of lobectomy (n = 8) or wedge resection (n = 2). Median follow-up post-SABR was 6.3 months. After combined treatment, the rate of acute grade 3–4 toxicity was 10%. There was no post-operative mortality at 90 days. The small sample size included herein precludes any definitive conclusions regarding overall toxicity rates until larger datasets are available. However, these data may inform others who are designing or conducting similar trials. Trial registration NCT02136355 . Registered 8 May 2014.